Case report: Combination therapy with selinexor, decitabine and half-dose CAG regimen for relapsed elderly acute myeloid leukemia - Zhang, Xueya; Sun, Yuqi; Zhong, Jinfa (Frontiers in Oncology, 2024)
The treatment of elderly patients diagnosed with acute myeloid leukemia (AML) poses significant challenges. Currently, one promising strategy in therapeutic interventions for geriatric individuals revolves around the utilization of small molecule targeted drugs either independently or in conjunction with demethylating agents. In this report, we present the successful attainment of complete remission in an elderly female patient with relapsed AML, the patient underwent treatment with a combination of Selinexor, decitabine, and a half-dose CAG regimen for two cycles. Subsequently, the patient has sustained this remission through consolidation therapy involving a medium dose of Ara-c. This therapeutic regimen has demonstrated favorable outcomes in the management of relapsed AML in elderly individuals. Furthermore, the adverse reactions were manageable. In order to devise an efficacious treatment regimen for elderly patients suffering from relapsed and refractory acute myeloid leukemia, it is imperative to incorporate a larger cohort of cases for clinical investigation.